2019
DOI: 10.3390/ijms21010196
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Late Effects of Early Weaning on Rat Gastric Cell Differentiation

Abstract: Background: Gastric glands grow and cells reach differentiation at weaning in rats. By considering that early weaning (EW) can affect the timing of development, we aimed to compare molecular and cellular markers of differentiation in pups and adults. Methods: Wistar rats were separated into suckling-control (S) and EW groups at 15 days. Stomachs were collected at 15, 18, and 60 days for RNA and protein extraction, and morphology. Results: After EW, the expression of genes involved in differentiation (Atp4b, Bh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 63 publications
(125 reference statements)
0
14
0
1
Order By: Relevance
“…Additionally, when niches were closely observed, a resilient proliferative activity remained higher at the base after EW, compared with the S group at 60 days. Such an area is a secondary compartment for epithelial proliferation (Han et al, 2019 ; Burclaff et al, 2020 ), and the residing zymogenic cell population is increased by EW (Teles Silva et al, 2020 ). Due to these combined data, we investigated some of the parameters that could be involved in cell trans-differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, when niches were closely observed, a resilient proliferative activity remained higher at the base after EW, compared with the S group at 60 days. Such an area is a secondary compartment for epithelial proliferation (Han et al, 2019 ; Burclaff et al, 2020 ), and the residing zymogenic cell population is increased by EW (Teles Silva et al, 2020 ). Due to these combined data, we investigated some of the parameters that could be involved in cell trans-differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Two times a day, EW rats received food and water through disposable Pasteur pipettes and were massaged to facilitate excretion, mimicking maternal care. The number of pups with the dam was controlled to avoid obesity, and the experiments proceeded when the body mass was observed to change according to the patterns previously established (Teles Silva et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EW and the change to solid food affect the development of pulmonary and GI tracts and interfere in cell proliferation and differentiation. In the gastric mucosa, EW stimulates cell proliferation through MAPK signaling (Cummins & Thompson, 2002; Osaki et al, 2011) and it interferes in cell differentiation (Zulian et al, 2017; Teles Silva et al, 2019). Similarly, we demonstrated that EW also reduces the differentiation of intestinal goblet cells in rats (da Costa et al, 2019).…”
Section: Breastmilk Composition and Its Antimicrobial Rolementioning
confidence: 99%